The Dravidian languages - Krishnamurti, Bhadriraju (Cambridge University Press, 2003)
The Dravidian languages are spoken by over 200 million people in South Asia and in Diaspora communities around the world, and constitute the world's fifth largest language family. It consists of about 26 languages in total including Tamil, Malayalam, Kannada and Telugu, as well as over 20 non-literary languages. In this book, Bhadriraju Krishnamurti, one of the most eminent Dravidianists of our time, provides a comprehensive study of the phonological and grammatical structure of the whole Dravidian family from different aspects. He describes its history and writing systems, discusses its structure and typology, and considers its lexicon. Distant and more recent contacts between Dravidian and other language groups are also discussed. With its comprehensive coverage this book will be welcomed by all students of Dravidian languages and will be of interest to linguists in various branches of the discipline as well as Indologists.